The Effect of Role Play Learning Model Based on Folk Stories for Speaking Skills at Grade III Students of SDN 122358 Pematangsiantar - Lusi Ardina Purba; Yanti Arasi Sidabutar; Sukardo Sitohang (International Journal of Technology and Education Research, 2026)
This study aims to determine the effect of role-playing learning model based on folklore on speaking skills of third grade students of SDN 122358 Pematangsiantar. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Pretest-Posttest Design. The research sample consisted of 23 students in the experimental class and 20 students in the control class. Data collection techniques used performance tests, observation, and documentation. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using Independent Samples T-Test. The results showed that the average posttest score of the experimental class was 88.70, higher than the average posttest score of the control class of 43.25. Based on the results of the hypothesis test, the Sig. (2-tailed) value was obtained at 0.000 <0.05 and the calculated t value > t table, which was 23.613 > 2.020, so Ho was rejected and Ha was accepted. Thus, it can be concluded that there is a significant influence of the folklore-based role-playing learning model on the speaking skills of third-grade students at SDN 122358 Pematangsiantar.